Feasibility of Higher Order Thinking Skill-Based on Descriptive Text Assessment Instruments Developed on 7th Grade Students of Junior High School (SMP Methodist Wesley Medan) - Lentare Pinta Sianturi; Biner Ambarita; Khairil Ansari (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
The development of a descriptive text assessment instrument must be considered in the regularity of the questions in accordance with the question grid. Based on the results of observations at Junior High School (SMP) Methodist Charles Wesley Medan, the teacher gave a questionnaire only in the form of essay questions (explanations) even though, in tests or tests carried out it was actually not just essays, but multiple choices. Feasibility of Higher Order Thinking Skill-Based Descriptive Text Assessment Instruments which is Developed on 7th Grade Students of Junior High School (SMP) Methodist Charles Wesley Medan is eligible and suitable for use in learning. Based on material experts, evaluation experts, Indonesian language teacher assessments and student responses